Band Offsets for Atomic Layer Deposited HfSiO4 on (Al0.14Ga0.86)2O3. (1st January 2018) - Fares, Chaker; Ren, F.; Lambers, Eric; Hays, David C.; Gila, B. P.; Pearton, S. J.
Abstract : There is increasing interest in (Alx Ga1-x )2 O3 /Ga2 O3 metal-oxide semiconductor field effect transistors, but there is little information on appropriate gate dielectrics for the (Alx Ga1-x )2 O3 . A potential candidate is HfSiO4 deposited by Atomic Layer Deposition (ALD), which should mitigate disruption to the surface. The valence band offset of the HfSiO4 /(Al0.14 Ga0.86 )2 O3 heterointerface was measured using X-Ray Photoelectron Spectroscopy. The single-crystal β-(Al0.14 Ga0.86 )2 O3 was grown by Molecular Beam Epitaxy. The bandgap of the HfSiO4 was determined by Reflection Electron Energy Loss Spectroscopy to be 7.0 ± 0.35 eV, while high resolution XPS data of the O 1s peak and onset of elastic losses was used to establish the (Al0.14 Ga0.86 )2 O3 bandgap as 5.0 ± 0.30 eV. The valence band offset was 0.42 eV ± 0.10 eV (straddling gap, type I alignment) for ALD HfSiO4 on β-(Al0.14 Ga0.86 )2 O3 . The conduction band offset was 1.58 ± 0.35 eV, providing good electron confinement.